APLIKASI STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO KECIL DAN MENENGAH (SAK-EMKM) PADA UMKM DI KECAMATAN TALANG KELAPA KABUPATEN BANYUASIN - Junaidi, Junaidi (Jemasi: Jurnal Ekonomi Manajemen dan Akuntansi, 2019)
This study aims to determine the application of accounting to MSMEs and analyze financial statement reporting using the SAK-EMKM approach. The sample used was 35 MSME food traders in Talang Kelapa District, Banyuasin Regency. The data used are primary data with data collection techniques using questionnaires and interviews. The analysis technique used is quantitative descriptive. The estimation results conclude that the application of accounting to UMKM food traders in Talang Kelapa still uses a simple method. MSMEs have not been able to apply the accounting cycle correctly. Of the 35 food traders who were sampled, there were only 2 traders who had applied accounting standards well. An understanding of the application of accounting standards needs to be socialized intensively to MSME traders in Talang Kelapa District.